2014
DOI: 10.1245/s10434-014-3978-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Malignant Peritoneal Mesothelioma: A Systematic Review and Meta-analysis

Abstract: While CRS + HIPEC has led to an improved survival for patients with MPM compared to historic data, heterogeneity of studies precludes generalizable inferences. EPIC chemotherapy and cisplatin chemoperfusion may infer survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(162 citation statements)
references
References 36 publications
3
153
0
6
Order By: Relevance
“…While there is scientific data to advocate the combination of cytoreductive surgery and perioperative intraperitoneal chemotherapy as treatment modality for peritoneal surface malignancies [33][34][35][36][37][38][39], the second component is still far from standardized. Significant variations in intraperitoneal chemotherapy remain and may influence the pharmacokinetics and pharmacodynamics of intraperitoneally delivered drugs, including their dose, the volume and the kind of carrier solution, the technique (open or closed abdomen), the intra-abdominal pressure and temperature, the duration of the intraperitoneal chemotherapy and the extent of (peritoneal) resections (Table 1) [3,18,40].…”
Section: Variables In Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…While there is scientific data to advocate the combination of cytoreductive surgery and perioperative intraperitoneal chemotherapy as treatment modality for peritoneal surface malignancies [33][34][35][36][37][38][39], the second component is still far from standardized. Significant variations in intraperitoneal chemotherapy remain and may influence the pharmacokinetics and pharmacodynamics of intraperitoneally delivered drugs, including their dose, the volume and the kind of carrier solution, the technique (open or closed abdomen), the intra-abdominal pressure and temperature, the duration of the intraperitoneal chemotherapy and the extent of (peritoneal) resections (Table 1) [3,18,40].…”
Section: Variables In Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…The early efforts of this multinational coalition to treat peritoneal mesothelioma should be recognized as the initial success of a global attack on this rare malignancy. This literature includes a systematic review and a meta-analysis [30,31]. A multidisciplinary conference in 2006 at the National Institutes of Health sponsored by the National Organization for Rare Diseases concluded that CRS plus perioperative chemotherapy may be considered by the multidisciplinary team as an initial treatment plan for patients with MPM [32].…”
Section: Normothermic Intraperitoneal Chemotherapy Long Term For Malimentioning
confidence: 99%
“…The most recent meta-analysis (twenty publications reporting on 1047 patients), complete crs was achieved in 67% of cases (range: 46%-93%), and pooled estimates of survival yielded 3-and 5-year os rates of 59% and 42% respectively 41 . The drugs used for hipec are doxorubicin, cisplatin, mitomycin C, and docetaxel.…”
Section: Malignant Peritoneal Mesotheliomamentioning
confidence: 99%
“…Prognostic factors for survival after crs and hipec include histologic subtype, proliferative index, lymph node status, disease burden, preoperative serum cancer antigen 125, completeness of crs, and major postoperative morbidity [40][41][42][43][44][46][47][48] . In a single preliminary study 49 , expression of Glut1 was the only factor independently associated with os in multivariate analysis.…”
Section: Malignant Peritoneal Mesotheliomamentioning
confidence: 99%